Quorum sensing modulators exhibit cytotoxicity in Hodgkin's lymphoma cells and interfere with NF-κB signaling. Issue 13 (1st July 2017) - Nandakumar, Natarajan; Dandela, Rambabu; Gopas, Jacob; Meijler, Michael M.
Graphical abstract: Abstract: In recent years it has become evident that bacteria can modulate signaling pathways in host cells through the secretion of small signaling molecules. We have evaluated the cytotoxic effects and NF-κB inhibitory activities of a panel of quorum sensing molecules and their reactive analogs on Hodgkin's lymphoma cells (L428). We found that several molecules inhibited NF-κB signaling in a dose dependent manner. Three inhibitors (ITC-12, ITC-Cl and Br-Furanone) showed 50% NF-κB inhibition at concentrations less than 10 µM (4.1 µM, 12.8 µM and 9.9 µM, respectively). Furthermore, all three molecules displayed cytotoxic effects against L428 cells with IC50 values of 12.4 µM, 18.3 µM and 3.1 µM respectively after 48 h incubation. They also showed inhibition of A549 adenocarcinoma cell migration at low concentrations 5.6 µM, 2.6 µM and 7.9 µM respectively. Further analysis showed that these molecules significantly decrease the degree of expression of proteins of NF-κB subunits p50, p65 and RelB both in cytosolic and nuclear fractions. This confirms that these compounds have the potential to modulate the NF-κB pathway by suppressing their subunits and thus exhibit cytotoxicity and inactivation of NF-κB signaling in Hodgkin's lymphoma cells.